A synthesis of the effects of summer interventions on secondary students with or at-risk of reading difficulties - Dille, Jordan T.; Capin, Phil; Daniel, Johny; Dille, Elena A.; Cahill, Alice S. (Frontiers in Education, 2025)
Students who are at-risk of academic underachievement demonstrate comparable academic growth to their typically developing peers during the academic school year. However, research has consistently shown that these students experience significant learning loss during the summer months, averaging a decline of 3–4 months of academic progress and knowledge. While substantial funding has been allocated to support summer instruction, there remains a lack of research specifically examining the impact of summer interventions for struggling readers at the secondary level. This synthesis systematically reviewed the effects of summer interventions with a reading component on the reading outcomes for students with, or at-risk of, reading difficulties in grades 6–12. Analysis of 13 studies revealed mixed results regarding the effectiveness of such interventions. Notably, teacher-led summer programs tended to be more effective than student-directed, home-based models that provided books without direct instruction. These findings highlight the critical need for more rigorous and targeted research on summer interventions for secondary students with or at-risk of reading difficulties.